Comparatively sonophotochemical and photochemical studies of phthalocyanines with cationic substituents on nonperipheral positions - Ozcesmeci, Mukaddes; Karanlik, Ceren can; Erdogmus, Ali; Hamuryudan, Esin (Tubitak Scientific & Technological Research Council Turkey, 2023)
The term sonophotodynamic therapy (SPDT) refers to a combination of sonodynamic therapy (SDT) and photodynamic therapy (PDT), in which the efficacy of the treatment is boosted by utilizing the proper amount of a sensitizer that is responsive to both light and ultrasound. Although it has been proven in photophysicochemical studies that SPDT enhances singlet oxygen production, related studies in the literature are very limited. Considering this situation, this study aims to investigate the efficacy of synthesized phthalocyanines in terms of PDT and SPDT. The singlet oxygen quantum values calculated as 0.13 for 5, 0.44 for 6, and 0.61 for 7 in photochemical (PDT) application increased to 0.18, 0.86, and 0.92, respectively, with sonophotochemical (SPDT) application. According to the results, singlet oxygen production was more efficient with SPDT. This work will add to the body of knowledge on employing the SPDT approach to increase singlet oxygen generation.
Keywords: Photodynamic therapy; phthalocyanine; singlet oxygen; sonophotodynamic therapy; DNA-BINDING; PHOTOPHYSICOCHEMICAL PROPERTIES; RECENT PROGRESS; THERAPY; ZINC(II); EFFICACY; GALLIUM; Chemistry; Engineering